Kaji Eksperimen Jarak Optimal Panen Energi Foton Bohlam LED untuk PV Polycrystalline - Mustofa, Mustofa (Program Studi Teknik Elektro Universitas Khairun, 2022)
LED type bulb light is generally widely used in building spaces in Indonesia today because it is more energy efficient than other types. The purpose of this study is to utilize the light bulb as a new photon energy source and free no night for a 50 Wp Solar PV panel that generates new electrical energy. Experimentally, it is to be known at what distance the best absorption of photon energy is between the light source and the PV panel. The results showed that the maximum power (0.1 Watt) was obtained at a distance of 20 cm with the 40 Watt Mavel LED type, while the highest efficiency (1.3%) with Philips bulb lightat a distance of 29 cmfrom the panel.The potential for the use of LED bulb light as lighting at night as well as as a new source of electrical energy –PLTBoh in closed indoor PV installations looks quite good. Therefore the incorporation of PV with solar energy during the day and bulb energy at night will help charging and storage of electrical energy on batteries for the availability of alternative electrical energy dc electronic devices even AC